Preliminary Study on Teachers' Use of the iPad in Bachelor of Education Program at a Private University in Malaysia - Yusup, Hashim; Yusri, Yusup (Springer International Publishing, 2014)
This paper examines the status of iPad (1st generation) use as a learning device among primary school teachers enrolled in an undergraduate bachelor of education program at a private university in Malaysia. A survey was conducted on 93 teachers who were given iPads to assist them in this online distance-learning program in the March 2011 semester. The result of the survey indicate that iPad has effective technical features and pedagogical tools that assisted the teachers in learning, particularly due to its lightweight, responsive touch-screen, text legibility as well as other mobility features. However, the tablet is highly dependent on the Internet and areas with no Wi-Fi make the iPad inadequate for teaching and learning. Regardless, most teachers prefer to use iPad compared to laptops for teaching and learning activities and believe that iPad is a good learning device to collaborate and share ideas among fellow users.